Neutropenic enterocolitis-induced sepsis and disseminated intravascular coagulation after chemotherapy: a case report - Masako Ishikawa; Kentaro Nakayama; Sultana Razia; Akiko Ishida; Hitomi Yamashita; Tomoka Ishibashi; Seiya Sato; Kiyoka Sawada; Hiroki Sasamori; Sonomi Kurose; Noriyoshi Ishikawa; Satoru Kyo (BMC, 2021)
Abstract Background Neutropenic enterocolitis (NE) is a potentially life-threatening disease that primarily occurs in cancer patients treated with chemotherapy. NE has substantial morbidity and mortality, and its incidence has increased with the widespread use of chemotherapeutic agents such as taxanes, gemcitabine, and leucovorin in patients with lung, breast, gastric, and ovarian cancers. Sometimes NE can be a possible cause of death. Although, conservative approaches are often successful, there are currently no standardized treatment guidelines for NE and it is unclear when such strategies should be implemented. Therefore, we present this report to provide a greater insight into the possible treatment of NE. Case presentation We report the case of a 72-year-old woman with endometrial cancer who was undergoing treatment for hypertension, obesity and diabetes mellitus. The patient initially developed paralytic ileus on the 6th postoperative day (POD) after surgery for endometrial serous carcinoma. Complete recovery was achieved after 4 days of fasting and fluid replacement therapy. On the 27th POD, she received the first cycle of combination chemotherapy consisting of paclitaxel and carboplatin. On day 5 of chemotherapy, she developed the systemic inflammatory response syndrome including febrile neutropenia and sepsis. She then developed disseminated intravascular coagulation (DIC) and septic shock. The patient was subsequently moved to the intensive care unit (ICU). Despite initiating the standard treatment for septic shock and DIC, her overall status worsened. It was assumed that gut distention had led to bowel damage, subsequently leading to bacterial translocation. Thus, she developed NE with severe DIC and septic shock. We decided to reduce the intestinal pressure using an ileus tube to suction the additional air and fluid, even though doing so had a risk of worsening her general condition. The inflammatory reaction subsided, and her general condition improved. The patient recovered after 18 days in the ICU and was discharged alive. Conclusions Herein, we describe a patient with suspected chemotherapy-associated NE. Our observations suggest that postoperative ileus may be one of the possible causes of NE. Patients who experience postoperative ileus must be carefully monitored while undergoing chemotherapy.